A High‐Efficiency CoSe Electrocatalyst with Hierarchical Porous Polyhedron Nanoarchitecture for Accelerating Polysulfides Conversion in Li–S Batteries. Issue 32 (28th June 2020) - Ye, Zhengqing; Jiang, Ying; Li, Li; Wu, Feng; Chen, Renjie
Abstract: Lithium–sulfur (Li–S) batteries are recognized as promising candidates for next‐generation electrochemical energy storage systems owing to their high energy density and cost‐effective raw materials. However, the sluggish multielectron sulfur redox reactions are the root cause of most of the issues for Li–S batteries. Herein, a high‐efficiency CoSe electrocatalyst with hierarchical porous nanopolyhedron architecture (CS@HPP) derived from a metal–organic framework is presented as the sulfur host for Li–S batteries. The CS@HPP with high crystal quality and abundant reaction active sites can catalytically accelerate capture/diffusion of polysulfides and precipitation/decomposition of Li2 S. Thus, the CS@HPP sulfur cathode exhibits an excellent capacity of 1634.9 mAh g −1, high rate performance, and a long cycle life with a low capacity decay of 0.04% per cycle over 1200 cycles. CoSe nanopolyhedrons are further fabricated on a carbon cloth framework (CC@CS@HPP) to unfold the electrocatalytic activity by its high electrical conductivity and large surface area. A freestanding CC@CS@HPP sulfur cathode with sulfur loading of 8.1 mg cm −2 delivers a high areal capacity of 8.1 mAh cm −2 under a lean electrolyte. This work will enlighten the rational design of structure–catalysis engineering of transition‐metal‐based nanomaterials for diverse applications. Abstract : A high‐efficiency CoSe electrocatalyst with hierarchical porous polyhedron nanoarchitecture (CS@HPP) is presented as a sulfur host for lithium–sulfur batteries. The CS@HPP with high electrical conductivity and abundant active sites can catalytically accelerate capture/diffusion of polysulfides and precipitation/decomposition of Li2 S. Consequently, excellent electrochemical performance is synchronously displayed for both slurry‐bladed and freestanding cathodes.